Automatic Iranian Vehicle License Plate Recognition System Based on Support Vector Machine (SVM) Algorithms - Mahdi Aghaie; Fatemeh Shokri; Meisam Yadolah Zade Tabari (Universitas Sriwijaya, 2013)
In the emerging trends the pervasive nature across the computing environment shows that the system is platform independent and device independent. The system development is designed with the help of Structured Query Language and middleware infrastructure that are used to collect the information from various nodes. An essential feature of this proposed middleware architecture suites the device independent as the major supporting capability to the system. This facilitates to add new device types in the system feels easy through the use of device self-description.Â It mainly focuses on the issues related to the heterogeneity of the different devices composing a pervasive system: This aspect is investigated both at data management and at physical integration levels. Using the nontrivial approach aims at handling the related issues are resolved with the corresponding solution. Keyword: Perla, Cloud Monitoring, Middleware, Declarative Language